Outcome of mini open anterolateral rotator cuff repair by suture anchor - Lingayat, M. B.; Sharma, Ramkripal; P. V., Vimal; Kakade, Rohan; Lakde, Shubham (International Journal of Research in Orthopaedics, 2024)
Background: Rotator cuff tears are a prevalent cause of shoulder pain and dysfunction, necessitating effective surgical interventions to restore function and alleviate symptoms. The mini open anterolateral rotator cuff repair technique using suture anchors has emerged as a promising approach, combining the advantages of arthroscopic and open surgery. This study aimed to evaluate the outcomes of mini open anterolateral rotator cuff repair with suture anchors, focusing on pain relief, range of motion, functional outcomes, complications, and radiographic assessments. Methods: A retrospective analysis was conducted on 30 patients who underwent mini open anterolateral rotator cuff repair. Patient demographics, surgical details, postoperative outcomes, complications, and radiographic findings were evaluated. Results: The average pain score significantly decreased from 7.8 (SD=1.2) preoperatively to 2.3 (SD=0.8) postoperatively (p<0.001). Range of motion improved with an average increase from 60 to 150 degrees of abduction and from 50 to 140 degrees of flexion (p<0.001). Functional outcomes, assessed by the American Shoulder and Elbow Surgeons (ASES) score, increased from 45 to 85 points (p<0.001). Complications, including joint stiffness, pain, and re-tears, were effectively managed. Radiographic assessments demonstrated satisfactory healing and alignment in the majority of patients. Conclusions: Mini open anterolateral rotator cuff repair with suture anchors is an effective and safe surgical approach for managing rotator cuff injuries, leading to improved clinical outcomes and favorable radiographic findings. Further research is warranted to validate these findings and optimize treatment strategies.